Influence of equilibration time and freezing diluent on post-thaw motility and acrosomal integrity of epididymal sperm from the African buffalo (Syncerus caffer) - Gerber, David (University of Pretoria, 2013)
Dissertation (MSc (Production Animal Science))--University of Pretoria, 2003.